The Implementation of Digital Humanities in the State Islamic University Libraries in Indonesia - Zain, Labibah; Anwar, Ahmad; Marwiyah; Hadna, Ida Nor’aini; Komarudin; Hannum, Ilma Nabilla Ashfia (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
State Islamic University libraries are striving to become research libraries. Since humanities are the core discipline in most State Islamic Universities, a new service concept—digital humanities—has been introduced to support research activities. This study explores the implementation of digital humanities in three State Islamic University libraries: UIN Sunan Kalijaga Yogyakarta, UIN Syarif Hidayatullah Jakarta, and UIN Maulana Malik Ibrahim Malang. This research employs a qualitative methodology, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that while the libraries have sufficient librarians, their involvement in research activities is not extensive or proactive. Additionally, the facilities and infrastructure necessary to support digital humanities are inadequate. Although policies supporting digital humanities exist, there is a lack of strategic programs to explore and fully enhance library use and involvement in research. Furthermore, internal cooperation between institutions has been established but remains limited, indicating a need for libraries to adopt a more proactive role. These insights underscore the challenges and opportunities in implementing digital humanities within State Islamic University libraries, providing a foundation for future strategic initiatives to enhance their research support capabilities.